Safety of a new extensively hydrolysed formula in children with cow's milk protein allergy: a double blind crossover study - Schaafsma Anne; Khouw Ilse MSL; Terheggen-Lagro Suzanne WJ; Wauters Erik AK (BMC, 2002)
Abstract Background Formulae for infants with cow's milk protein allergy (CMA) should be based on extensively hydrolysed protein. 'Extensively' however is not strictly defined. Differences in molecular weight and peptide chain length may affect its clinical outcome. We studied the safety of a new extensively hydrolysed casein based formula (Frisolac Allergycare®: FAC) for children with IgE mediated CMA. Methods Thirty children, aged 1.5 - 14.8 years old (median 4.9 years) with persistent CMA were enrolled in this double-blind reference product (Nutramigen®: NUT) controlled crossover study. All had positive skin prick tests (SPT) and IgE mediated allergy, showing immediate reactions after ingestion of small amounts of milk. Twenty-five children also had positive radio allergen sorbent tests (RAST) to cow's milk. Formulae provided consisted of 80% elementary formula in combination with 20% reference or test product. Crossover periods lasted for two weeks. From both products molecular weight (MALDI-TOF method and HPLC) and peptide chain length distribution (adapted Edman degradation) were determined. Results Maximum molecular weights of NUT and FAC are 2.1 and 2.56 kDa, respectively. The contribution of free amino acids and small peptides <0.5 kDa is 46% for FAC and 53% for NUT. About 50% of the protein fraction of both products consists of peptides longer than four amino acids. Three children did not complete the study. The other children all tolerated FAC very well; no adverse reactions were reported. Conclusions The new extensively hydrolysed casein-based formula (FAC) can safely be used in children with IgE mediated cow's milk allergy.